Method for preparing high-crystallinity modified carbon nitride at low temperature, modified carbon nitride and application thereof

Through the low-temperature molten salt method and phosphorus doping method, the problem of insufficient photocatalytic performance of graphite phase carbon nitride is solved, wide spectrum response and high carrier separation efficiency are achieved, significantly improving photocatalytic performance and reducing energy Consumption and cost.

CN119218942APending Publication Date: 2024-12-31SHENZHEN UNIV
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411136606.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-08-19
Publication Date
2024-12-31

AI Technical Summary

Technical Problem

The narrow light absorption range of graphite phase carbon nitride (g-C3N4) in photocatalytic reaction and severe carrier recombination leads to its low photocatalytic activity and efficiency.

Method used

Highly crystalline modified carbon nitride was prepared by low-temperature molten salt method. By mixing urea, solar salt and phosphonochloride trimers, the synthesis temperature is reduced and the phosphorus doping is used to broaden the light absorption range and increase the Carrier separation efficiency.

Benefits of technology

The wide spectrum response and high carrier separation efficiency are achieved, the photocatalytic performance of carbon nitride is significantly improved, the manufacturing energy consumption and cost are reduced, and the photocatalytic hydrogen peroxide production is improved by 27 times.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119218942A_ABST
    Figure CN119218942A_ABST
Patent Text Reader

Abstract

The invention provides a method for preparing high-crystallinity modified carbon nitride at low temperature, and belongs to the technical field of photocatalytic materials.The method comprises the steps that urea, solar salt and phosphonyl chloride tripolymer are mixed and then ground, and a mixture is obtained; calcining the mixture at the temperature of 300 to 400 DEG C to obtain a calcined product; performing washing and vacuum drying on the calcined product to obtain high-crystallinity modified carbon nitride; wherein in the mixture, the mass ratio of the urea to the solar salt to the phosphonyl chloride tripolymer is 20: 4: 1. The modified carbon nitride prepared by the method has the advantages of wide spectral response and high carrier separation efficiency, so that the modified carbon nitride has excellent photocatalytic performance, the synthesis temperature of the modified carbon nitride in the method is relatively low, and the modified carbon nitride has the advantages of low energy consumption and low cost. The invention also provides high-crystallinity modified carbon nitride and application thereof.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of photocatalytic materials, and particularly relates to a method for preparing highly crystalline modified carbon nitride at low temperature, the modified carbon nitride and applications thereof. Background Art

[0002] Scientific and technological innovation is an important means to solve environmental problems. In order to cope with environmental and energy problems, scientific researchers are committed to exploring new technologies and materials in the field of environmental protection and clean energy, such as photocatalysis and renewable energy technologies, in order to alleviate environmental and energy pressures through scientific innovation. Hydrogen peroxide is considered to be a promising solar fuel. As a substitute for traditional fossil fuels, its energy density is 3.0MJ / L (60vol% hydrogen peroxide), which is comparable to the energy density of compressed hydrogen (35MPa) of 2.8MJ / L. In addition, hydrogen peroxide does not require high-pressure tank storage. As an energy storage medium, it is superior to hydrogen in terms of stability and portability, so it has been used in fuel cells and rockets. In fuel cells, hydrogen peroxide is used as a reactant at the cathode and anode, and the theoretical output voltage can be as high as 1.09V without any pollutant emissions. The generation of hydrogen peroxide through photocatalysis can utilize renewable light energy, and during the implementation process, no external oxidant needs to be added, thereby achieving the goal of sustainable energy utilization and environmental friendliness.

[0003] Hydrogen peroxide is a strong oxidant with important application value in many fields such as environmental purification, wastewater treatment, and organic synthesis. Hydrogen peroxide plays an important role in the field of disinfection and sterilization. As a broad-spectrum antibacterial agent, it is widely used in the disinfection of medical devices, sewage treatment, and food processing. In the specific application of environmental purification, hydrogen peroxide can decompose complex organic pollutants into harmless or low-toxic substances through its strong oxidation effect, thereby helping to reduce the concentration of harmful substances in the environment. In addition, it can also react with certain heavy metal ions to form precipitates that are difficult to dissolve in water, thereby reducing the harm of these heavy metals to the environment. In the process of wastewater treatment, hydrogen peroxide can not only directly oxidize organic pollutants, but also be used in combination with other chemical reagents to improve the efficiency and effect of wastewater treatment. It is the application of hydrogen peroxide in many aspects that has led to an increase in the demand for hydrogen peroxide year by year. It is estimated that China's demand will reach 23.79 million tons by 2025. The anthraquinone method is currently the most mature and widely used method for synthesizing hydrogen peroxide. In industrial production, up to 95% of hydrogen peroxide is prepared by this method. However, the anthraquinone method produces waste gas and waste liquid during the production process, which have a serious impact on the environment. The main components of the waste gas include hydrogen peroxide vapor and aromatic hydrocarbon vapor, while the waste liquid is mainly an organic solution composed of 2-ethylanthraquinone, heavy aromatic hydrocarbons and trioctyl phosphate. If these substances are not handled properly, they will cause serious damage to the ecological environment. In order to solve this problem, the method of photocatalytic production of hydrogen peroxide has gradually attracted attention. This method uses clean light energy to drive the reaction of water and oxygen to generate hydrogen peroxide. Photocatalytic reactions usually do not require high temperature or high pressure conditions, so they can be carried out in a relatively mild environment. Compared with traditional chemical methods, photocatalytic technology avoids the generation of harmful byproducts and realizes a green and environmentally friendly oxidation reaction. Through the study of photocatalytic production of hydrogen peroxide, it is expected to solve environmental pollution problems, improve energy efficiency, and promote sustainable development, which is of great significance to the fields of environment, energy and materials science.

[0004] Graphitic carbon nitride (g-C3N4) is a functional material that has attracted much attention and has been widely studied for its good photocatalytic performance. This material has cheap and abundant raw materials, high chemical stability, and excellent electrical and thermal conductivity, making it have potential application value in many fields. However, despite these excellent properties, g-C3N4 also has some problems that need to be solved: first, the light absorption range of g-C3N4 is relatively narrow, which limits its application in photocatalytic reactions; second, severe carrier recombination and low efficiency of photogenerated charge separation are also important factors affecting its photocatalytic activity. These problems lead to low photocatalytic activity and photocatalytic efficiency of g-C3N4. Summary of the invention

[0005] In order to solve the problem of insufficient photocatalytic performance of g-C3N4, the present invention provides a method for preparing highly crystalline modified carbon nitride at low temperature. The modified carbon nitride prepared by this method has the advantages of wide spectral response and high carrier separation efficiency, and thus has excellent photocatalytic performance. In addition, the synthesis temperature of the modified carbon nitride in this method is low, which has the advantages of low energy consumption and low cost.

[0006] The invention also provides a highly crystalline modified carbon nitride and application thereof.

[0007] The present invention is achieved through the following technical solutions:

[0008] The present invention provides a method for preparing high-crystalline modified carbon nitride at low temperature, the method comprising:

[0009] urea, solar salt and phosphonyl chloride trimer are mixed and ground to obtain a mixture;

[0010] calcining the mixture at 300-400° C. to obtain a calcined product;

[0011] The calcined product is washed and vacuum dried to obtain highly crystalline modified carbon nitride;

[0012] Among them, in the mixture, the mass ratio of urea, solar salt and phosphonyl chloride trimer is 20:4:1.

[0013] Further, the urea, solar salt and phosphonyl chloride trimer are mixed and then ground to obtain a mixture, which specifically includes:

[0014] Urea, solar salt and phosphonyl chloride trimer are mixed and ground for 10 to 20 minutes to obtain a mixture.

[0015] Further, the mixture is calcined at 300-400° C. to obtain a calcined product, which specifically includes:

[0016] The mixture is calcined at 300-400° C., with a heating rate of 2° C. / min and a heat preservation time of 2-6 hours, and then naturally cooled to room temperature to obtain a calcined product.

[0017] Furthermore, the calcined product is washed and vacuum dried to obtain a highly crystalline modified carbon nitride, specifically comprising:

[0018] The calcined product is washed with 80-100° C. water for several times, and then vacuum dried at 60±10° C. for 12±2 h to obtain highly crystalline modified carbon nitride.

[0019] Based on the same inventive concept, the present invention provides a highly crystalline modified carbon nitride, which is prepared by the above-mentioned method for preparing highly crystalline modified carbon nitride at low temperature.

[0020] Based on the same inventive concept, the present invention also provides an application of highly crystalline modified carbon nitride in photocatalytic synthesis of hydrogen peroxide.

[0021] One or more technical solutions in the embodiments of the present invention have at least the following technical effects or advantages:

[0022] 1. The present invention provides a method for preparing highly crystalline modified carbon nitride at low temperature. The method uses solar salt (60% NaNO3 and 40% KNO3) as molten salt, and copolymerizes phosphonyl chloride trimer as a phosphorus source with urea to achieve phosphorus doping, wherein the solar salt reduces the synthesis temperature of carbon nitride, so that urea can be thermally polymerized at low temperature (300°C-400°C) to prepare carbon nitride, thereby reducing energy consumption, while also reducing the band gap, broadening the absorption spectrum of carbon nitride, reducing the carrier recombination rate and improving the separation and migration efficiency of photogenerated charges, and improving the crystallinity of carbon nitride. The doping of phosphorus further reduces the band gap, broadens the light absorption range of carbon nitride, improves the utilization rate of visible light, and improves the separation and migration efficiency of photogenerated carriers. The method uses urea, phosphonyl chloride trimer and solar salt to prepare modified carbon nitride with wide spectral response and high carrier separation efficiency at low temperature, thereby achieving the purpose of improving the photocatalytic performance of carbon nitride and reducing the manufacturing energy consumption and cost of carbon nitride.

[0023] 2. The highly crystalline modified carbon nitride of the present invention is prepared by mixing and grinding urea, a phosphonyl chloride trimer and a solar salt and then calcining the mixed carbon nitride. The modified carbon nitride has the advantages of a wide spectrum response and a high carrier separation efficiency. The photocatalytic performance is greatly improved after being modified with solar salt and a phosphonyl chloride trimer. The performance of photocatalytic production of hydrogen peroxide is improved by 27 times. The synthesis temperature of the modified carbon nitride is low, and it has the advantages of low energy consumption and low cost. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] In order to more clearly illustrate the technical solutions in the embodiments of the present invention, the following briefly introduces the drawings required for use in the description of the embodiments. Obviously, the drawings described below are some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.

[0025] Figure 1 is the X-ray diffraction pattern of the carbon nitride material of the present invention.

[0026] Figure 2 This is a Fourier transform infrared spectrum of the carbon nitride material of the present invention.

[0027] Figure 3 This is the ultraviolet-visible diffuse reflectance spectrum of the carbon nitride material of the present invention.

[0028] Figure 4 Graph showing the bandgap width of the carbon nitride material of the present invention.

[0029] Figure 5 This is the Mott-Schottky diagram of the carbon nitride material of the present invention.

[0030] Figure 6 Schematic diagram of the energy band structure of the carbon nitride material of the present invention.

[0031] Figure 7 This is a photoluminescence spectrum of the carbon nitride material of the present invention.

[0032] Figure 8 This is a time-resolved transient photoluminescence spectrum of the carbon nitride material of the present invention.

[0033] Fig. 9 This is the instantaneous response photocurrent diagram of the carbon nitride material of the present invention.

[0034] Fig.10 This is a performance diagram of photosynthetic hydrogen peroxide of the carbon nitride material of the present invention.

[0035] Fig.11 This is the performance diagram of photosynthetic hydrogen peroxide of U-SS-P with different phosphorus contents.

[0036] Fig.12 Performance diagram of U-SS-P photosynthetic hydrogen peroxide at different synthesis temperatures.

[0037] Fig.13 This is the performance diagram of photosynthetic hydrogen peroxide of U-SS-P doped with different phosphorus sources.

[0038] Fig.14 This is a high-resolution transmission electron microscope image of the carbon nitride material of the present invention. DETAILED DESCRIPTION

[0039] The present invention will be described in detail below in conjunction with specific implementations and examples, and the advantages and various effects of the present invention will be more clearly presented. It should be understood by those skilled in the art that these specific implementations and examples are used to illustrate the present invention, rather than to limit the present invention.

[0040] Throughout the specification, unless otherwise specifically stated, the terms used herein should be understood as meanings commonly used in the art. Therefore, unless otherwise defined, all technical and scientific terms used herein have the same meanings as those generally understood by those skilled in the art to which the present invention belongs. In the event of a conflict, the present specification takes precedence.

[0041] Unless otherwise specified, various raw materials, reagents, instruments and equipment used in the present invention can be purchased from the market or prepared by existing methods.

[0042] The technical principle of the present invention is as follows:

[0043] At present, many strategies have been applied to improve the photocatalytic performance of g-C3N4, including heteroatom doping, defect engineering, surface modification, and heterostructure construction. Among them, the preparation of graphite phase carbon nitride by molten salt method has become a hot topic in current research. Usually, in order to obtain highly crystalline carbon nitride, it is necessary to prepare it under high temperature conditions of 500 to 600 °C. However, this high-temperature thermal polymerization method will lead to a significant increase in energy consumption, thereby increasing production costs. In contrast, the molten salt method can significantly reduce the synthesis temperature due to its uniform heating and excellent thermal conductivity. In addition, the graphite phase carbon nitride prepared by the molten salt method is often accompanied by heteroatom doping, which helps to improve the carrier separation efficiency and charge transfer performance of the catalyst. At present, the molten salts commonly used in the molten salt method mainly include sodium chloride (NaCl), potassium chloride (KCl), lithium chloride (LiCl) and lithium nitrate (LiNO3). However, the melting temperature range of these molten salts is limited, and the cost of some molten salts is high. Therefore, it is urgent to develop a low-cost molten salt with a large melting temperature range.

[0044] The present invention adopts solar salt (60% NaNO3 and 40% KNO3) as molten salt to prepare carbon nitride by thermal polymerization of urea at low temperature (300°C-400°C), while also reducing the carrier recombination rate and improving the separation efficiency of photogenerated charges. Phosphonyl chloride trimer is further used as a phosphorus source to achieve phosphorus doping during the thermal polymerization of carbon nitride, thereby broadening the light absorption range of carbon nitride, improving the utilization rate of visible light, and effectively improving the photocatalytic performance of carbon nitride.

[0045] The method for preparing high-crystalline modified carbon nitride at low temperature of the present invention comprises:

[0046] S1. mixing urea, solar salt and phosphonyl chloride trimer and grinding to obtain a mixture;

[0047] S2. calcining the mixture at 300 to 400 ° C to obtain a calcined product;

[0048] S3. The calcined product is washed and vacuum dried to obtain a highly crystalline modified carbon nitride;

[0049] Among them, in the mixture, the mass ratio of urea, solar salt and phosphonyl chloride trimer is 20:4:1.

[0050] In the present invention, the optimal mass ratio of urea, solar salt and phosphonyl chloride trimer is 20:4:1. The advantage of using this ratio for solar salt is that it ensures a high degree of polymerization of carbon nitride at low temperatures, and the advantage of using this ratio for phosphorus oxychloride trimer is that it can be doped with a suitable concentration of phosphorus, thereby improving the photocatalytic performance of the catalyst.

[0051] Step S1 specifically includes:

[0052] Urea, solar salt and phosphonyl chloride trimer are mixed and ground for 10 to 20 minutes to obtain a mixture.

[0053] Step S2 specifically includes:

[0054] The mixture is calcined at 300-400° C., with a heating rate of 2° C. / min and a heat preservation time of 2-6 hours, and then naturally cooled to room temperature to obtain a calcined product.

[0055] In the present invention, the heating rate of the mixture calcination is 2°C / min, and the holding time is 2 to 6 hours. The holding time affects the polymerization degree of carbon nitride. The advantage of the holding time of 2 to 6 hours is that the holding time increases the polymerization degree of carbon nitride and improves the porosity.

[0056] Step S3 specifically includes:

[0057] The calcined product is washed with 80-100° C. water for several times, and then vacuum dried at 60±10° C. for 12±2 h to obtain highly crystalline modified carbon nitride.

[0058] In the present invention, the benefit of washing the calcined product with water at 80-100° C. is that potassium nitrate and sodium nitrate are salts that are easily soluble in water, and their solubility in water increases with increasing temperature. Hot water is used to increase the solubility of solar salt (60% NaNO3 and 40% KNO3) in water, and to ensure that excess solar salt can be washed away during washing.

[0059] The following will describe in detail the method for preparing highly crystalline modified carbon nitride at low temperature, the modified carbon nitride and its application in combination with the embodiments and experimental data.

[0060] Example 1

[0061] The method of preparing high-crystalline modified carbon nitride at low temperature in this embodiment comprises:

[0062] (1) Weigh 10 g of urea, 2 g of solar salt, and 0.5 g of phosphonyl chloride trimer, put them into a mortar, and grind them for 10 min to obtain a mixture.

[0063] (2) placing the mixture in a muffle furnace for calcination, heating it to 375° C. at a rate of 2° C. / min, keeping the temperature for 2 h, and then naturally cooling it to room temperature to obtain a calcined product.

[0064] (3) The calcined product was washed with 100° C. boiling water for three times, and then vacuum dried in a 60° C. vacuum drying oven for 12 h to obtain highly crystalline modified carbon nitride.

[0065] Example 2

[0066] This example characterizes the highly crystalline modified carbon nitride.

[0067] 1. X-ray diffraction analysis of carbon nitride material was performed using an X-ray diffractometer to obtain the following Figure 1 XRD pattern shown.

[0068] Figure 1 The preparation process of the catalysts represented by U550, U375, U-SS and U-SS-P is as follows:

[0069] U375: Weigh 10g of urea and put it into a crucible. The crucible is placed in a muffle furnace for calcination. The temperature is raised to 375℃ at a rate of 2℃ / min, and the temperature is kept for 2 to 6 hours. Then, it is naturally cooled to room temperature to obtain a calcined product.

[0070] U550: Weigh 10g of urea and put it into a crucible. The crucible is placed in a muffle furnace for calcination. The temperature is raised to 550℃ at a rate of 2℃ / min, and the temperature is kept for 2 to 6 hours. Then, the crucible is naturally cooled to room temperature to obtain a calcined product.

[0071] U-SS: (1) Weigh 10 g urea and 2 g solar salt, put them into a mortar and grind for 10-20 min.

[0072] (2) The mixture is placed in a crucible and placed in a muffle furnace for calcination. The temperature is raised to 375° C. at a rate of 2° C. / min, and the mixture is kept at this temperature for 2 to 6 hours. The mixture is then naturally cooled to room temperature to obtain a calcined product.

[0073] (3) The calcined product was washed with 100° C. boiling water for three times, and then vacuum dried in a 60° C. vacuum drying oven for 12 h to obtain highly crystalline modified carbon nitride.

[0074] U-SS-P: The synthesis method is the same as in Example 1.

[0075] The method for synthesizing U-SS-P is the same as that for synthesizing U-SS-P. The amount of phosphonyl chloride trimer added is controlled to control the phosphorus doping ratio. The amount of urea and solar salt is kept unchanged. 0.5 g, 0.75 g, 1 g, 1.5 g, and 2 g of phosphonyl chloride trimer are added respectively to prepare U-SS-P. 0.5 , U-SS-P 0.75 , U-SS-P1, U-SS-P 1.5 , U-SS-P2.

[0076] The catalyst was prepared by changing the synthesis temperature in the same way as the method for synthesizing U-SS-P. The amounts of urea, solar salt and phosphonyl chloride trimer were kept constant, and calcination was performed at 350°C, 375°C and 400°C, respectively, to prepare U-SS-P350, U-SS-P375 and U-SS-P400.

[0077] In the typical XRD pattern of carbon nitride (U550) fired at 550°C, two characteristic diffraction peaks can be seen at 2θ=13.8° and 27.6°. The peak at 13.8° corresponds to the (100) crystal plane diffraction peak formed by the accumulation of carbon nitride within the plane, and the peak at 27.6° corresponds to the (002) crystal plane diffraction peak formed by the accumulation of carbon nitride layers. From the figure, it can be seen that when the firing temperature is 375°C (U375), there is no peak at 13.8°, but there is a peak at 10.6°. The peak at 10.6° is the characteristic peak of Melem, which is the result of incomplete thermal polymerization due to low temperature. After adopting the molten salt method (U-SS), the peak at 10.6° disappeared, indicating that the thermal polymerization was complete during the reaction process. We used solar salt to lower the temperature for preparing carbon nitride and the energy consumption for material preparation. In addition, the diffraction peak of the (002) crystal plane after molten salt treatment is sharper and stronger than that of pure carbon nitride, which indicates that the crystallinity of carbon nitride is increased after molten salt treatment. After further introduction of phosphorus doping (U-SS-P), the peak intensity of (002) becomes lower, the half-peak width also becomes larger, and the crystallinity of carbon nitride is destroyed. This indicates that phosphorus doping will destroy the crystallinity of carbon nitride, but lattice fringes can be seen in the high-resolution transmission electron microscope image, which proves that it still has crystallinity after phosphorus doping.

[0078] 2. The carbon nitride material was characterized by Fourier transform infrared spectroscopy. The results are as follows Figure 2 shown.

[0079] From the Fourier transform infrared spectrum of carbon nitride catalyst, we can see that each sample has a wavelength of 810 cm -1 There is a peak at 1200-1700cm, which is the stretching vibration peak caused by the isotriazine structure. This shows that the molten salt method and phosphorus doping did not destroy the structure of carbon nitride. -1 The peaks in 2900-3500cm are derived from the stretching vibration of aromatic CN heterocycles. -1 The broad peak at 2172 cm is due to the vibration of residual NH and OH, which may be caused by the amino groups at the edge of carbon nitride and the absorbed water molecules. Compared with U375 and U550, U-SS-P has two obvious differences. One is that U-SS-P has a -1 A new peak appears at the bottom, which is the vibration peak of the cyano group; the other is that the vibration peak intensity of NH is reduced. These two differences indicate that some of the edge amino groups in the modified carbon nitride are converted into cyano groups.

[0080] 3. The carbon nitride material was characterized by UV-visible diffuse reflectance spectroscopy. The results are as follows: Figure 3 , 4 shown.

[0081] In the process of photocatalysis, the first step is that the catalyst absorbs light with energy greater than or equal to the bandgap width, and is stimulated to generate photogenerated electron-hole pairs. This step is crucial to the entire photocatalytic process because photogenerated electrons and holes are the key to participating in subsequent chemical reactions. Therefore, the light absorption performance of the catalyst has a decisive influence on its photocatalytic activity. We use UV-visible diffuse reflectance spectroscopy to detect the light absorption performance of the catalyst. Figure 3 From the light absorption spectrum, the light absorption sideband of U550 is 440nm, the light absorption range of U375 is the smallest, and the absorption sideband is 418nm. After the molten salt method, the light absorption sideband is widened to 460nm, and after phosphorus doping, it is widened to a maximum of 467nm. According to the Kubelka-Munk formula, the bandgap width of the catalyst is calculated. The bandgap width of U375 is 2.84eV, the bandgap width of U550 is 2.65eV, the bandgap width of U-SS is 2.51eV, and the bandgap width of U-SS-P is 2.48eV. Phosphorus-doped carbon nitride (U-SS-P) prepared by the molten salt method shows a wider visible light absorption range, improves the utilization rate of visible light, and generates more photogenerated carriers during illumination, which is one of the reasons for the improvement of photocatalytic performance. The change in the visible light absorption range is consistent with the color of the sample. The colors of U375 and U550 are white, the color of U-SS is yellow, and the color of U-SS-P becomes dark yellow.

[0082] 4. The photoelectrochemical properties of the photocatalyst were measured using an electrochemical workstation (CHI760E, Shanghai Chenhua Instrument Co., Ltd.). Figure 5 , 6 shown.

[0083] To determine the conduction band position, we used the Mott-Schottky spectrum to estimate the flat band potential (E fb ). The Mott Schottky spectrum shows that carbon nitride is a typical n-type semiconductor. According to the intersection of the tangent on the X-axis, we calculated that the flat band potential of the sample is -1.20eV, -1.19eV, -1.24eV, -1.31eV (vs. Ag / AgCl), corresponding to U375, U550, U-SS, and U-SS-P, respectively. According to the formula E NHE =E Ag / AgCl +0.197V, the flat band potentials of the above samples are further converted to -1.00eV, -0.99eV, -1.04eV, -1.11eV (vs. NHE). For n-type semiconductors, their conduction band positions are generally 0.1-0.3eV more negative than the flat band potential. Therefore, it is estimated that the conduction band positions of U375, U550, U-SS, and U-SS-P are -1.10eV, -1.09eV, -1.14eV, and -1.21eV (vs. NHE) respectively. According to E VB=E g +E CB , and the band structure of the prepared sample was obtained.

[0084] 5. The carbon nitride material was characterized by photoluminescence spectroscopy. The results are as follows: Figure 7 , 8 shown.

[0085] The molten salt method and phosphorus doping can not only improve the light absorption performance of the material, but also affect the separation and migration of photogenerated carriers. We tested PL and TR-PL to explore the charge migration dynamics of the catalyst. Figure 7 As shown in the figure, U375 has the highest peak intensity. The high PL intensity can be attributed to the shortened conjugation length, which limits the separation of excitons. After the molten salt method, the peak intensity decreases, and the peak intensity is the lowest when the molten salt method is combined with phosphorus doping, indicating that there are fast-recombining carriers inside the carbon nitride. The molten salt method and phosphorus doping can effectively reduce this recombination rate. The reduction of the electron-hole recombination rate is conducive to improving the separation and migration efficiency of carriers. Therefore, the molten salt method and phosphorus doping have a positive effect on improving charge separation.

[0086] The carrier lifetimes of the samples are well fitted by a biexponential function consisting of a fast decay component and a slow decay component. The fast decay component originates from a non-radiative process involving photoinduced electron capture, while the slow decay component is attributed to the interband recombination of free excitons. The average carrier lifetime of U375 is 9.28ns, that of U550 is 4.11ns, and that of U-SS is 2.10ns. U-SS-P has the shortest average lifetime of 1.98ns, with a shorter τ ave This indicates that there is a charge migration path that effectively separates exciton pairs, and it has the best carrier separation and migration effects.

[0087] 6. The photoelectrochemical properties of the photocatalyst were measured using an electrochemical workstation (CHI760E, Shanghai Chenhua Instrument Co., Ltd.). Fig. 9 shown.

[0088] Detection method: The transient response photocurrent was tested using a three-electrode electrolytic cell of an electrochemical workstation, with a platinum sheet as the counter electrode, an Ag / AgCl electrode in a saturated potassium chloride solution as the reference electrode, a catalyst deposited on a conductive glass as the working electrode, and a 0.2 mol / L sodium sulfate aqueous solution as the electrolyte. The preparation method of the working electrode is as follows: 10 mg of the sample was dispersed in 0.5 mL of N,N-dimethylformamide, 50 microliters of a 0.05% Nafion aqueous solution was added, and a suspension was obtained by ultrasonic treatment. 20 microliters of the suspension was transferred to a 1×1 cm 2On the conductive glass. After drying at 80℃ for 12h, the working electrode was obtained. When testing with an electrochemical workstation, the current-time curve was selected and a bias of 0.6V was added when setting the parameters. Fig. 9 The transient response photocurrent diagram is shown.

[0089] Instantaneous response photocurrent is one of the important means to evaluate the efficiency of photogenerated carrier separation. In the present invention, we show the current-time (it) diagram under five cycles of switching illumination. It can be clearly observed from the figure that the U-SS-P sample modified by molten salt treatment and phosphorus doping shows a higher current density. This result shows that the separation efficiency of photogenerated carriers by molten salt method and phosphorus doping has been significantly improved.

[0090] The above experimental results show that the modification of carbon nitride materials not only improves the separation efficiency of photogenerated carriers, but also promotes more photogenerated carriers to participate in the preparation of hydrogen peroxide, thereby increasing the yield of hydrogen peroxide. In addition, the results of the photocurrent test are consistent with the previous photoluminescence test results, further verifying the improvement of carrier separation efficiency.

[0091] Example 3

[0092] This example tests the performance of carbon nitride materials in photocatalytic synthesis of hydrogen peroxide.

[0093] 1. Photocatalytic hydrogen peroxide production experiment, the specific experimental steps are as follows:

[0094] 10 mg of the prepared catalyst was evenly dispersed in 36 mL of water and poured into a quartz bottle. 4 ml of isopropanol was added as a sacrificial agent. The quartz bottle was sealed with a rubber stopper and ultrasonically dispersed for 5 min. Oxygen was continuously passed for 10 min in the dark. The quartz bottle was placed in a multi-channel reaction system and irradiated under visible light with an average light intensity of 100 mW / cm 2 . Test method for hydrogen peroxide concentration: Every 30 minutes, take out 2 mL of the reaction solution and remove the photocatalyst with a 0.22 μm microporous filter. Add 1 mL of 0.4 mol / L potassium iodide solution and 1 mL of 0.1 mol / L potassium hydrogen phthalate aqueous solution to 2 mL of the above solution, and then keep in the dark for 30 minutes. Due to the reaction between iodine ions and hydrogen peroxide, the colorless solution shows color and exhibits strong absorption near 350 nm. The absorbance at 350 nm was measured by UV-visible spectroscopy to calculate the total amount of hydrogen peroxide produced during the photocatalytic reaction. The results are as follows: Fig.10 The equipment used: PCX-50C Discover multi-channel photocatalytic reaction system (Beijing Perfect Light Technology Co., Ltd.), Cary 5000 UV-Vis-NIR spectrophotometer (Agilent Technologies Co., Ltd.).

[0095] Fig.10 The performance of each catalyst in photocatalytic hydrogen peroxide production is shown in the figure. After three hours of illumination, the concentration of photocatalytic hydrogen peroxide production of U-SS-P reached 4236μmol / L, and the production of U375, U550 and U-SS reached 60μmol / L, 155μmol / L and 615μmol / L, respectively. The photocatalytic performance of U-SS-P is 70 times higher than that of U375, 27 times higher than that of U550, and 6.8 times higher than that of U-SS. The improvement in photocatalytic performance is due to the synergistic effect of the molten salt method and phosphorus doping. These two modification strategies give U-SS-P a wide spectral absorption range and efficient photogenerated carrier separation and transfer efficiency.

[0096] 2. Use U-SS-P with different P contents to photocatalytically synthesize hydrogen peroxide.

[0097] This example further explores the relationship between the amount of phosphorus doping and the amount of hydrogen peroxide produced. The results are as follows: Fig.11 The same synthesis method as in Example 1 was used to control the amount of phosphonyl chloride trimer added to control the phosphorus doping ratio, and the amounts of urea and solar salt were kept unchanged. 0.5 g, 0.75 g, 1 g, 1.5 g, and 2 g of phosphonyl chloride trimer were added respectively to prepare U-SS-P 0.5 , U-SS-P 0.75 , U-SS-P1, U-SS-P 1.5 The prepared material was tested for its photocatalytic performance by producing hydrogen peroxide (the test method was the same as step 1 in Example 3). Fig.11 It can be seen that U-SS-P 0.5 The yield of U-SS-P was the highest, reaching 4236 μmol / L in three hours. 0.75 The yield was 2133 μmol / L, the yield of U-SS-P1 was 1516 μmol / L, and the yield of U-SS-P 1.5 The yield was 282 μmol / L, and the yield of U-SS-P2 was 46 μmol / L.

[0098] 3. Photocatalytic synthesis of hydrogen peroxide using U-SS-P prepared at different synthesis temperatures.

[0099] This example explores the relationship between synthesis temperature and hydrogen peroxide production. The results are as follows Fig.12As shown. The same synthesis method as in Example 1 was used to prepare the catalyst by changing the synthesis temperature. The amounts of urea, solar salt and phosphonyl chloride trimer were kept unchanged, and calcination was performed at 350°C, 375°C and 400°C respectively to prepare U-SS-P350, U-SS-P375 and U-SS-P400. The prepared materials were tested for their photocatalytic performance by producing hydrogen peroxide (the test method was the same as in step 1 of Example 3). Fig.12 It can be seen that the yield of U-SS-P375 is the highest under three hours of illumination, reaching 4236μmol / L, the yield of U-SS-P350 is 184μmol / L, and the yield of U-SS-P400 is 3524μmol / L.

[0100] 4. Photocatalytic synthesis of hydrogen peroxide using U-SS-P prepared from different phosphorus sources.

[0101] U-SS-P photocatalytic materials were prepared using different phosphorus sources, specifically including:

[0102] (1) Weigh 10 g of urea, 2 g of solar salt, and 0.5 g of a phosphorus source (ammonium dihydrogen phosphate or ammonium hypophosphite or guanidine phosphate), put the three into a mortar, and grind for 10 minutes to obtain a mixture.

[0103] (2) placing the mixture in a muffle furnace for calcination, heating it to 375° C. at a rate of 2° C. / min, keeping the temperature for 2 h, and then naturally cooling it to room temperature to obtain a calcined product.

[0104] (3) The calcined product was washed with 100° C. boiling water for three times, and then vacuum dried in a 60° C. vacuum drying oven for 12 h to obtain a catalyst.

[0105] The three catalysts prepared were used to catalyze the production of hydrogen peroxide. The method for producing hydrogen peroxide was the same as step 1 of Example 3. The performance results of the hydrogen peroxide production obtained were shown in the figure below: Fig.13 shown.

[0106] from Fig.13 It can be seen that the photocatalytic performance of phosphorus doped with different phosphorus sources is different. The best effect is the phosphonyl chloride trimer. After three hours of illumination, the production of hydrogen peroxide reaches 4236μmol / L. The production of ammonium hypophosphite is the worst, only 212μmol / L, the production of guanidine phosphate is 384μmol / L, and the production of diammonium phosphate is 1118μmol / L.

[0107] Fig.14 This is a high-resolution transmission electron microscope image of U-SS-P. From the image, we can see that U-SS-P has obvious lattice fringes, which indicates that the material is still crystalline after phosphorus doping.

[0108] Finally, it should be noted that the terms "comprises," "includes," or any other variations thereof are intended to cover non-exclusive inclusion, such that a process, method, article, or apparatus that includes a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements that are inherent to such process, method, article, or apparatus.

[0109] Although the preferred embodiments of the present invention have been described, those skilled in the art may make other changes and modifications to these embodiments once they have learned the basic creative concept. Therefore, the appended claims are intended to be interpreted as including the preferred embodiments and all changes and modifications that fall within the scope of the present invention.

[0110] Obviously, those skilled in the art can make various changes and modifications to the present invention without departing from the spirit and scope of the present invention. Thus, if these modifications and variations of the present invention fall within the scope of the claims of the present invention and their equivalents, the present invention is also intended to include these modifications and variations.

Claims

1. A method for preparing highly crystalline modified carbon nitride at low temperature, characterized in that: The method comprises: urea, solar salt and phosphonyl chloride trimer are mixed and ground to obtain a mixture; calcining the mixture at 300-400° C. to obtain a calcined product; The calcined product is washed and vacuum dried to obtain highly crystalline modified carbon nitride; Among them, in the mixture, the mass ratio of urea, solar salt and phosphonyl chloride trimer is 20:4:

1.

2. The method for preparing high-crystalline modified carbon nitride at low temperature according to claim 1, characterized in that: The method of mixing urea, solar salt and phosphonyl chloride trimer and grinding them to obtain a mixture specifically comprises: Urea, solar salt and phosphonyl chloride trimer are mixed and ground for 10 to 20 minutes to obtain a mixture.

3. The method for preparing high-crystalline modified carbon nitride at low temperature according to claim 1, characterized in that: The step of calcining the mixture at 300-400° C. to obtain a calcined product specifically comprises: The mixture is calcined at 300-400° C., with a heating rate of 2° C. / min and a heat preservation time of 2-6 hours, and then naturally cooled to room temperature to obtain a calcined product.

4. The method for preparing high-crystalline modified carbon nitride at low temperature according to claim 1, characterized in that: The calcined product is washed and vacuum dried to obtain a highly crystalline modified carbon nitride, specifically comprising: The calcined product is washed with 80-100° C. water for several times, and then vacuum dried at 60±10° C. for 12±2 h to obtain highly crystalline modified carbon nitride.

5. A highly crystalline modified carbon nitride, characterized in that: The highly crystalline modified carbon nitride is prepared by the method for preparing highly crystalline modified carbon nitride at low temperature according to any one of claims 1 to 4.

6. Use of the highly crystalline modified carbon nitride as claimed in claim 5 in photocatalytic synthesis of hydrogen peroxide.

Citation Information

Patent Citations

  • Phosphor sulfur co-doped graphite phase carbon nitride photo-catalyst, preparation method and application thereof

    CN106669759A

  • Catalyst for synthesis of hydrogen peroxide by catalyzing oxygen reduction under visible light and preparation method thereof

    CN109012728A

  • Phosphorus and bismuth co-doped porous graphite-phase carbon nitride photocatalyst and use thereof

    CN109772423A

  • Method for preparing high-crystallinity polymer carbon nitride at low temperature by using solar salt and application of high-crystallinity polymer carbon nitride

    CN116920906A